Different lubricating oil treatments for the determination of Cu, Cr, Fe, Ni, Sb, Pb, and Zn by HR-CS FAAS - Resta, Volnei [UNESP]; Filho, Amorim [UNESP]; Gomes Neto, José Anchieta [UNESP] (Taylor & Francis Inc, 2008)
Microwave-assisted acid decomposition, direct dilution in kerosene, and oil-in-water emulsion were evaluated as lubricating oil pretreatment procedures for Cu, Cr, Fe, Ni, Pb, Sb, and Zn determination by High-Resolution Continuum Source Flame Atomic Absorption Spectrometry (HR-CS FAAS). For wet digestion, results were compared with those obtained by Flame Atomic Absorption Spectrometry (FAAS). The ultrasound probe used in emulsions sonication contaminated samples with Cr, although better results have been observed for the other six elements in this condition. In general, recovery percentages ranging from 81-106%(Cu), 80-107%(Cr), 85-114%(Fe), 82-116%(Ni), 86-117%(Pb), 85-115%(Sb), and 81-114%(Zn) were obtained. The HR-CS FAAS showed to be faster and more sensitive than FAAS.
Keywords: HR-CS FAAS; lubricating oil; metals; sample preparation